Nonsteroidal anti-inflammatory drugs and cardiovascular disease risk in spondyloarthritis-spectrum diseases. Issue 4 (July 2022) - So, Ho; Tam, Lai-Shan
Abstract : Purpose of review: Increased cardiovascular (CV) risk associated with nonsteroidal anti-inflammatory drugs (NSAIDs) is well recognized in the general population. This may limit the use of this effective therapy in patients with spondyloarthritis (SpA), a population already at high CV risk. Recent findings: Increased CV diseases and their risk factors in patients with SpA were consistently shown in recent population-level data. NSAIDs remained commonly prescribed in SpA, though their structural benefit remained controversial and the dispensing practice was variable in different regions in the world. A previous observation study suggested NSAIDs in SpA might be cardio-protective, possibly via their modulation of the chronic inflammatory state. A recent meta-analysis of nonrandomized studies also revealed no increased risk of a CV event. Interestingly, there is growing evidence that different NSAIDs might impose differential CV risk on patients with SpA. Summary: Recent evidence suggested NSAIDs were associated with a neutral and possibly lower CV risk in patients with SpA, which provided some reassurance for their use.